2017
DOI: 10.1016/j.vaccine.2017.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation-related loss of antigen-specific IFNγ producing CD4+ T-cells can skew immunogenicity data in vaccine trials: Lessons from a malaria vaccine trial substudy

Abstract: Ex vivo functional immunoassays such as ELISpot and intracellular cytokine staining (ICS) by flow cytometry are crucial tools in vaccine development both in the identification of novel immunogenic targets and in the immunological assessment of samples from clinical trials. Cryopreservation and subsequent thawing of PBMCs via validated processes has become a mainstay of clinical trials due to processing restrictions inherent in the disparate location and capacity of trial centres, and also in the need to standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…Despite of minor protocol changes compared with our previously published method including the use of lithium heparin anticoagulation and Leucosep ™ tubes to standardise cell isolation, the results of the present study confirmed previous evidence that cryopreservation of PBMCs in RPMI supplemented with autologous serum facilitates excellent recovery of CD154 + A. fumigatus‐ specific T cells . By contrast, flow cytometric detection of IFN‐γ + cells showed lower concordance of fresh and frozen cells and a tendency towards reduced detection rates in frozen cells, matching previous observations on Plasmodium falciparum TRAP peptide reactive T‐helper cells . Cryopreservation of PBMCs using AIM‐V or FCS‐supplemented RPMI resulted in poor performance of CD154‐ and IFN‐γ‐based‐specific T‐cell quantification, with high unspecific background and weak correlation with immediately processed samples.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite of minor protocol changes compared with our previously published method including the use of lithium heparin anticoagulation and Leucosep ™ tubes to standardise cell isolation, the results of the present study confirmed previous evidence that cryopreservation of PBMCs in RPMI supplemented with autologous serum facilitates excellent recovery of CD154 + A. fumigatus‐ specific T cells . By contrast, flow cytometric detection of IFN‐γ + cells showed lower concordance of fresh and frozen cells and a tendency towards reduced detection rates in frozen cells, matching previous observations on Plasmodium falciparum TRAP peptide reactive T‐helper cells . Cryopreservation of PBMCs using AIM‐V or FCS‐supplemented RPMI resulted in poor performance of CD154‐ and IFN‐γ‐based‐specific T‐cell quantification, with high unspecific background and weak correlation with immediately processed samples.…”
Section: Discussionsupporting
confidence: 88%
“…Differences in susceptibility of T‐cell subsets to cryopreservation may explain the broad bandwidth of assay performance in thawed samples . In particular, CD4 + cells were reported to exhibit greater susceptibility to cryopreservation than CD8 + cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study showed that the frequency of antigen-specific CD4 + T cells detected by cytokine secretion was significantly reduced (between three and five-fold) after cryopreservation; ICS or ELISpot using thawed cells showed lower and more CD8-biased responses than those using PBMC ex vivo [ 50 ]. The ability to perform T cell assays using cryopreserved cells is crucial in many clinical trials—particularly those involving multiple centres.…”
Section: Discussionmentioning
confidence: 99%
“…This is because there is evidence from a malaria vaccine study that antigen-specific IFNγ producing CD4 + T-cells were reduced three to five-fold after freeze-thaw compared with fresh. However, CD8 + populations remained mostly unaffected [ 94 ]. This effect may not be seen for viral antigens, as fresh and frozen PBMCs were used in ELIspot assays in an HIV vaccination study [ 95 ].…”
Section: Quantifying T-cell Memory At Different Stages Of Vaccine mentioning
confidence: 99%